If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8 + -3x = 5x + -4 Reorder the terms: 8 + -3x = -4 + 5x Solving 8 + -3x = -4 + 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. 8 + -3x + -5x = -4 + 5x + -5x Combine like terms: -3x + -5x = -8x 8 + -8x = -4 + 5x + -5x Combine like terms: 5x + -5x = 0 8 + -8x = -4 + 0 8 + -8x = -4 Add '-8' to each side of the equation. 8 + -8 + -8x = -4 + -8 Combine like terms: 8 + -8 = 0 0 + -8x = -4 + -8 -8x = -4 + -8 Combine like terms: -4 + -8 = -12 -8x = -12 Divide each side by '-8'. x = 1.5 Simplifying x = 1.5
| 5-t=-6 | | 2(-4y-6)= | | y=1380.00+8(1380.00) | | 9-3x=9-8x | | 9y^2=25y+6 | | x^2+0.06x-0.028=0 | | 2(-4-6)= | | -0.204(800)+0.8=0.07(8000) | | 4x5/7 | | 15x+21y=25 | | -6(-3)=v | | 10=45-n | | y=1.8(1380.00) | | F(X)=COSX | | 3(6z-1)-5(z+8)=8(z+1) | | 0=-5t^2+30t+50 | | 7-18n=2 | | y=1.08(1380.00) | | 10+7x=5-3x | | 9-3(-3N+1)=2(-3N+4)+13 | | 3-3p+7p=19 | | 12+r/2=112 | | y=0.92(1380.00) | | 11[10-11(y-10)]=220 | | -7-2(5+4f)= | | 6y+v=6v | | X(x+7)=-6 | | 7W+2+W+3-3W-8=-2W+11 | | 2(-1/2+3/4)= | | 14+5x=6x | | 11u-9u=6 | | (8m-2)(8m+2)= |